Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 11 - 11.2 - Arithmetic Sequences and Partial Sums - 11.2 Exercises - Page 786: 24



Work Step by Step

The $nth$ term of an arithmetic sequence is given by: $a_n=a_1+(n-1)d$ If $a_1=0,~~d=-\frac{2}{3}$: $a_n=0+(n-1)(-\frac{2}{3})=-\frac{2}{3}n+\frac{2}{3}=\frac{-2n+2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.